PENGARUH TRANSFORMASI DIGITAL TERHADAP KINERJA OPERASIONAL PERBANKAN DI INDONESIA - Pranita, Fera Lufhidarani; Nurfitri, Ade Rachmawati; Jasa, Retnowati; Soukotta, Agnes; Jimar, Any (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the impact of digital transformation on banking operations in Indonesia. Digital transformation has become a strategic issue in the banking industry along with the development of information technology and the increasing public demand for fast, easy, and efficient financial services. This study uses a quantitative approach with an explanatory design to examine the relationship between digital transformation as the independent variable and operational performance as the dependent variable. The data used are secondary data obtained from the annual reports and financial statements of banks in Indonesia that have implemented digital services. The sampling technique used purposive sampling, while data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) using SmartPLS software. The results show that digital transformation has a positive and significant impact on banking operational performance. Increased service digitalization, technology investment, and digital innovation have been proven to improve operational cost efficiency, productivity, and customer service quality. These findings indicate that digital transformation plays a strategic role in improving operational performance and generating savings in banking in the digital era. However, the effectiveness of digital transformation is also influenced by the readiness of human resources, technological infrastructure, and management support in managing organizational change